Getting to the Heart of Connective Tissue Diseases - Rizzo, Toni (MD Conference Express, 2014)
Primary cardiac disorders in patients with connective tissue diseases are a consequence of the autoimmune process. Myocarditis evolving into dilated cardiomyopathy is a common complication of many connective tissue disorders, including systemic lupus erythematosus and systemic sclerosis. Other cardiac disorders associated with autoimmune diseases include endomyocarditis and endomyocardial fibrosis, pericarditis, valvulitis, hypertensive cardiomyopathy, and coronary arteritis. This article discusses the characterization, diagnosis, and management of these cardiovascular complications.